Sekolah Perempuan RAKAT as an Effort to Enhance Women’s Communication Capacity - Rahma, Amelia; Hafizah, Sarah Noor; Azizah, Isma; Fitriani, Fitriani; Ramadhiani, Nurhalisa; Azizah, Dhiya Alfi; Agusetiawan, Muhammad Andrian (Universitas Lambung Mangkurat, 2025)
This study aimed to evaluate the effectiveness of communication skills training through the Sekolah Perempuan RAKAT program in Banjar Regency, South Kalimantan. Many women in rural areas face challenges in public speaking, including limited mastery of effective communication techniques and low self-confidence. To address this issue, the program implemented a series of activities comprising registration, a pre-test, delivery of materials on effective communication, focus group discussions (FGDs), ice-breaking activities, experience-sharing sessions, a post-test, and closing activities. A total of 15 participants took part in the program. Data were collected through pre-test and post-test questionnaires and analyzed using the Shapiro–Wilk test for normality and the Wilcoxon signed-rank test to examine paired differences. The results showed that the data were not normally distributed (p < 0.05); therefore, the Wilcoxon test was applied. Statistical analysis indicated a significant increase in participants’ communication skills after the intervention (p<0.05). Qualitative findings also revealed improvements in participants’ understanding of communication strategies, active listening, empathetic responses, gender perspectives in communication, and the management of miscommunication. Furthermore, the experience-sharing sessions fostered mutual support and enhanced self-efficacy, contributing to increased confidence in public speaking. In conclusion, the Sekolah Perempuan RAKAT program effectively improved participants’ communication capacity and self-confidence. These findings highlight the importance of participatory and context-based approaches, such as FGDs, in empowering women to communicate more effectively in public spheres.